Access to international justice - Keyzer, Patrick 1966-; Popovski, Vesselin; Sampford, C. J. G. (Charles J. G.) (Routledge/challenges of globalisation, 2015)
There is much debate about the scope of international law, its compatibility with individual state practice, its enforceability and the recent and limited degree to which it is institutionalized. This collection of essays seeks to address the issue of access to justice, the related element of domestic rule of law which does not yet figure significantly in debates about international rule of law. Even in cases in which laws are passed, institutions are present and key players are ethically committed to the rule of law, those whom the laws are intended to protect may be unable to secure protection. This is an issue in most domestic jurisdictions but also one which poses severe problems for international justice worldwide. The book will be of interest to academics and practitioners of international law, environmental law, transitional justice, international development, human rights, ethics, international relations and political theory